2008
DOI: 10.1002/cncr.23688
|View full text |Cite
|
Sign up to set email alerts
|

Influence of induction chemotherapy and class of cytotoxics on pathologic response and survival after preoperative chemoradiation in patients with carcinoma of the esophagus

Abstract: BACKGROUND.Patients with localized esophageal cancer (LEC) have diverse outcomes (post‒therapy pathologic response, disease‒free survival [DFS], and overall survival [OS]) after preoperative chemoradiation (P‒CTRT), dictated also by inherent molecular heterogeneity. Whether the type of therapy influences the outcomes remains largely unanswered. It is hypothesized that induction chemotherapy (IC) or the type of cytotoxics used would not influence patient outcomes.METHODS.In this retrospective analysis, consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…Limitations of this report include: comparison of nonrandomized populations, retrospective nature of the analysis, small number of patients, patients treated in different time frames, and investigator bias. However, their data are consistent with a recent publication from the Duke University on 109 patients [22] and 180 patients from my center [9]. On the other hand, in another unpublished analysis of 360+ patients from my center, the use of a taxane in patients with localized carcinoma of the esophagus treated with preoperative chemoradiation lead to a survival advantage.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Limitations of this report include: comparison of nonrandomized populations, retrospective nature of the analysis, small number of patients, patients treated in different time frames, and investigator bias. However, their data are consistent with a recent publication from the Duke University on 109 patients [22] and 180 patients from my center [9]. On the other hand, in another unpublished analysis of 360+ patients from my center, the use of a taxane in patients with localized carcinoma of the esophagus treated with preoperative chemoradiation lead to a survival advantage.…”
supporting
confidence: 79%
“…These drugs are added or removed from further investigation based solely on empiricism; we finish the trial and get disappointed as usual. None of us has a clue as to what combination is better and until we do, perhaps we should choose the ones that are well tolerated [9]. Blinded use of targeted agents cannot quench our desire for rapid progress because the targeted agents act only if certain alterations exist within the tumor [10,11].…”
mentioning
confidence: 99%
“…However, this potential superiority was not found in a retrospective comparative study [17] and two prospective randomized phase II studies [27, 29]. One study suggested that only patients with stage III and IVa (and not stage II) disease who received induction chemotherapy had a significant survival advantage over preoperative CRT alone [16].…”
Section: Discussionmentioning
confidence: 99%
“…The backbone of induction chemotherapy generally consisted of a fluoropyrimidine (intravenous 5-FU or oral capecitabine) and oxaliplatin, with the addition of either leucovorin (54 % of cases) or docetaxel (37 % of cases) [17, 27]. Other (sporadic) induction chemotherapy regimens included carboplatin/paclitaxel (3 %), cisplatin/paclitaxel (1.5 %), cisplatin/irinotecan (1.5 %), 5-FU monotherapy (1.5 %) and capecitabine/oxaliplatin/epirubicin (1.5 %).…”
Section: Methodsmentioning
confidence: 99%
“…5 The prognosis for advanced GEC remains extremely poor, and overall 5-year survival rates are approximate 15%. 1,6 Cytotoxicchemotherapyremainsthemainstay of treatment for patients with incurable disease, 7 and targeted therapeutics are assuming an increasingly important role.…”
Section: Introductionmentioning
confidence: 99%